Change of voltage-gated potassium channel 1.7 expressions in monocrotaline-induced pulmonary arterial hypertension rat model - Hyeryon Lee; Kwan Chang Kim; Young Mi Hong (Korean Pediatric Society, 2018)
Purpose Abnormal potassium channels expression affects vessel function, including vascular tone and proliferation rate. Diverse potassium channels, including voltage-gated potassium (Kv) channels, are involved in pathological changes of pulmonary arterial hypertension (PAH). Since the role of the Kv1.7 channel in PAH has not been previously studied, we investigated whether Kv1.7 channel expression changes in the lung tissue of a monocrotaline (MCT)-induced PAH rat model and whether this change is influenced by the endothelin (ET)-1 and reactive oxygen species (ROS) pathways. Methods Rats were separated into 2 groups: the control (C) group and the MCT (M) group (60 mg/kg MCT). A hemodynamic study was performed by catheterization into the external jugular vein to estimate the right ventricular pressure (RVP), and pathological changes in the lung tissue were investigated. Changes in protein and mRNA levels were confirmed by western blot and polymerase chain reaction analysis, respectively. Results MCT caused increased RVP, medial wall thickening of the pulmonary arterioles, and increased expression level of ET-1, ET receptor A, and NADPH oxidase (NOX) 4 proteins. Decreased Kv1.7 channel expression was detected in the lung tissue. Inward-rectifier channel 6.1 expression in the lung tissue also increased. We confirmed that ET-1 increased NOX4 level and decreased glutathione peroxidase-1 level in pulmonary artery smooth muscle cells (PASMCs). ET-1 increased ROS level in PASMCs. Conclusion Decreased Kv1.7 channel expression might be caused by the ET-1 and ROS pathways and contributes to MCT-induced PAH.